AB0088 The role of high mobility group box-1 (HMGB1) in inflammatory vasculopathy in collagen antibody-induced arthritis (CAIA). (15th June 2017) - Biscetti, F; Flex, A; Angelini, F; Gremese, E; Tolusso, B; Ferraccioli, G
Abstract : Background: Rheumatoid arthritis (RA) is associated with vascular disease (1). Recent findings demonstrated that the risk of peripheral arterial occlusive disease is increased in patients with RA compared to the general population (2). However, the pathogenesis is not fully understood. High-mobility group box-1 (HMGB1) is a nuclear protein involved in inflammatory responses (3) and RA-like synovitis (4). Objectives: Aim of the present study was to analyze the relationship between HMGB1 and peripheral arterial disease in collagen antibody-induced arthritis (CAIA). Methods: BALB/c mice were injected with monoclonal anti-collagen antibody cocktail followed by lipopolysaccharide to induce arthritis. After the induction of arthritis, we studied ischemia-induced neovascularization in the ischemic hind limb of arthritic and control mice. Results: We found that the perfusion recovery was significantly attenuated arthritic mice, compared to control mice. The immunohistochemical analysis for the CD31 demonstrated a reduced number of vessel in mice with experimental arthritis. The selective blockade of HMGB1 in arthritic mice resulted in restored blood flow recovery and capillary density in the ischemic muscle. Cytokine enzyme-linked immunosorbent assay (ELISA) analyses performed on peripheral blood demonstrated a significant reduction of interleukin (IL)-1β, IL-6 and tumor necrosis factor (TNF)-α in mice where HMGB1 was blocked. Interestingly, the selective blockade of HMGB1 resulted in an increase of the peripheral IL-17A concentration. Conclusions: HMGB1 pathway is involved in an experimental vasculopathy induced in a RA-like model. The proangiogenic cytokine IL-17A is increased when HMGB1 is inhibited. Although further data are needed, these findings provide new evidence regarding the pathogenesis of vascular complications observed in patients with RA. References: Roman MJ, Salmon JE. Cardiovascular manifestations of rheumatologic diseases. Circulation. 2007 Nov 13;116(20):2346–55. Chuang YW, Yu MC, Lin CL, Yu TM, Shu KH, Huang ST, Kao CH. Risk of peripheral arterial occlusive disease in patients with rheumatoid arthritis. A nationwide population-based cohort study. Thromb Haemost. 2016 Jan;115(2):439–45. Biscetti F, Ghirlanda G, Flex A. Therapeutic potential of high mobility group box-1 in ischemic injury and tissue regeneration. Curr Vasc Pharmacol. 2011 Nov;9(6):677–81. Biscetti F, Flex A, Pecorini G, Angelini F, Arena V, Stigliano E, Gremese E, Tolusso B, Ferraccioli G. The role of high-mobility group box protein 1 in collagen antibody-induced arthritis is dependent on vascular endothelial growth factor. Clin Exp Immunol. 2016 Apr;184(1):62–72. Disclosure of Interest: None declared